Implementasi Sistem Rekam Medis Pasien Menggunakan Pendekatan Customer Relationship Management (CRM) - Wiyanto Wiyanto; Fajar Butsianto; Karsito Karsito (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2018)
Information technology is rapidly developed in this century that impact to various aspects of the organization really need information technology to support the performance and everyday business processes. In health services, information technology is required to process and storage the patient medical records, so that the patient's medical record is well preserved, and competitive advantage can be obtained between patient and polyclinic. The application of Customer Relationship Management (CRM) approach can be developed by implementing information system of medical record history to get new patient and retain existing patient, improving relationship with patient and maintaining patient loyalty as well as supporting the company/organization to provide excellent service to customers in real time through the advantage of information technology. The aims of this research are to understand patient medical record by CRM approach and Unified Modeling Language (UML) for system design, system validation using Forum Group Discussion (FGD), and using software testing Model ISO 9126. The result of this research are Medical Record History Information System and the result of system validation with FGD is 100% accepted, the result of system test using Model ISO 9126 is good with success rate 82,86%, so it can give contribution to polyclinic.